A theoretical model influencing the use of pre-exposure prophylaxis in MSM population: a qualitative study from Beijing - Yongbing Sun; Bing Song; Chengqi Liu; Ziyi Lu; Juan Cheng; Tianjun Jiang (Journal of Men's Health)
Background: Men who have sex with men (MSM) represent a key population in China’s efforts to reduce the spread of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS). Despite the effectiveness of pre-exposure prophylaxis (PrEP) as a preventive measure, its utilization rate among MSM in China remains notably low. Methods: This qualitative study investigated factors influencing PrEP usage among MSM in Beijing following the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. A total of 10 MSM participants were included based on the principle of information saturation. The data were analyzed using Nvivo 10 software based on the Grounded Theory approach, with a coding process consisting of first-level, second-level and third-level coding. Results: Several key factors were identified as influencing the adoption of PrEP, including medication side effects, dosing frequency, co-existing sexually transmitted infections, participation in high-risk sexual behaviors and partner attitudes. Additionally, factors such as sexual impulses, understanding of PrEP, economic considerations, and accessibility to purchasing locations also played significant roles. These factors were categorized into three main groups: individual factors, sexual factors and social environmental factors. Based on these findings, a theoretical model was developed to depict the interconnected pathways that influence PrEP utilization among MSM. Conclusions: The findings suggest that social workers can play an important role in addressing the barriers to PrEP adoption identified in the model and recommend enhancing the involvement of community workers to facilitate the promotion and uptake of PrEP among MSM.